The new home : a handbook for tenants (London : The Health and Cleanliness Council, 1937)
1937 1937 1930s 24 pages : illustrations [illustration] The all-electric kitchen planned for easy working. KITCHEN PLANNING Save waste of energy by arranging your kitchen so that everything in it is handy. Prevent stooping and backache by having the kitchen table higher than an ordinary table. You will probably have to take the sink as you find it. But if you have a say in the matter, see that the sink is of the height that is best for your use. TABLE-TOPS MUST BE KEPT SPECIALLY CLEAN The ideal kitchen table has a washable top of enamel. Otherwise the top should be covered in washable material, and other tables should be frequently polished. Polish makes a smooth surface from which to wipe off dust. MAKE YOUR "WASHING-UP" EASY Before putting greasy plates into soapy water, scrape them with a knife on to a piece of paper. This will save your dish-cloth and keep the sink cleaner. All vessels which have contained milk should first be rinsed in cold water and then washed in hot water. [illustration] Scrape grease off plates. 9 177/5/8/2